Anthropogenic reverberations on the gut microbiome of dwarf chameleons (Bradypodion) - Adair,Matthew G.; Tolley,Krystal A.; van Vuuren,Bettine Jansen; da Silva,Jessica Marie (PeerJ, 2025)
Exploration of the microbiome has been referred to as a final frontier in biological research. This is due to its precedence for generating insights on the holistic functioning of organismal biology by exploring the interactions between hosts and their associated symbiotic organisms. The microbiomes of many vertebrate groups still require exploration to advance current knowledge and fill previous knowledge gaps. This study generated initial descriptions of the bacterial microbiomes of three species of dwarf chameleon (Bradypodion) from the 16S rRNA gene region targeting the V3 and V4 hypervariable regions. This led to the successful identification of 1,073 and 4,502 independent amplicon sequence variants from buccal swab and faecal material samples, respectively. This newly acquired information is intended as a baseline for future work incorporating holobiont information. The diversity of microbial taxa suggests that the total dwarf chameleon microbiome is similar to other squamates investigated to date, as well as chelonians (Testudines). Microbial frequency differences were noted in comparison to crocodilians (Archosauria) and mammalian groups. Furthermore, this study aimed to examine the influence of habitat transformation on the composition of the microbiome in dwarf chameleons as each of the study species occupy both urban and natural habitats. Given that most urban habitats are highly transformed, the expectation was that microbial assemblages of the gastro-intestinal tracts of all three Bradypodion species would show significant differences between populations (i.e., natural, or urban). It was found, however, that the level of effect was contingent on species: B. melanocephalum populations showed noticeable microbiome differences between urban and natural populations; B. thamnobates showed variations in microbial community dispersions between populations; and B. setaroi showed no significant microbiome differences based on diversity metrics although some frequency differences, in microbiome composition, were observed between populations. We suggest that the magnitude of difference between the habitats occupied by the populations is a factor, given the apparent disparity between the natural and urban habitats for B. melanocephalum as compared to the other two species.
Keywords: Metabarcoding; Small reptiles; Bacteriome; Microbiota; Natural vs. urban habitats; South Africa